Synteza Układów Wibroizolacji z Kompensacją - Cempel, C. (Engineering Transactions, 1973)
A general theory of vibro-insulation systems with compensation is presented. It is shown that the vibro-insulation effect may also be considered as invariance of the system with respect to disturbances. Depending on the type of compensation systems, the vibro-insulation systems may be invariant to all types of disturbances or to a class of harmonic disturbances. As an example, the behaviour of a system with inertial compensation is considered. It is proved that the inertial compensation effect improves the vibro-insulating properties of the system in the both cases of harmonic excitations and narrow-band random excitations.